2023
DOI: 10.3390/polym15112486
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Energy Storage Performance of PMMA/PVDF Composites by Changing the Crystalline Phase through Heat Treatment

Abstract: In today’s contemporary civilization, there is a growing need for clean energy focused on preserving the environment; thus, dielectric capacitors are crucial equipment in energy conversion. On the other hand, the energy storage performance of commercial BOPP (Biaxially Oriented Poly‒propylene) dielectric capacitors is relatively poor; hence, enhancing their performance has drawn the attention of an increasing number of researchers. This study used heat treatment to boost the performance of the composite made f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“… Comparison of the energy density U d and charge/discharge efficiency η of this work’s PVTC/BOPP(67%) bilayer film and previously reported results [ 22 , 34 , 35 , 36 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. …”
Section: Figuresupporting
confidence: 61%
See 1 more Smart Citation
“… Comparison of the energy density U d and charge/discharge efficiency η of this work’s PVTC/BOPP(67%) bilayer film and previously reported results [ 22 , 34 , 35 , 36 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. …”
Section: Figuresupporting
confidence: 61%
“…In order to further investigate the factors that influence energy storage, the breakdown performance of the bilayer film was tested. Following a linear fit of the data, the Weibull distribution curve was generated [ 34 , 35 ], as shown in Figure 2 c. The data analysis has revealed that the introduction of linear polymers results in an increase in the breakdown field strength ( E b ) of the PVTC/BOPP bilayer film relative to the pristine PVTC film (ca. 350 kV/mm).…”
Section: Resultsmentioning
confidence: 99%
“…For the 80PVDF/20PMMA blend matrix, the marginal changes in the lower frequency range εʹ values attributed to some variations in the polarization contributed by Maxwell-Wagner-Sillars (MWS) type interfacial polarization (IP) process. A slow decrease in εʹ values with the increase of frequency is expected because of the similar type of dielectric dispersion behaviour of the pure PVDF film [46,58,62] and a little change in the εʹ values of pristine PMMA film in the same frequency range [31,41,46]. This IP effect represents the accumulation of some long to short distance travelled charges at the interface regions of the polymer crystallites and amorphous domains and also the polymer and nanoclay interfaces [15,25,28,63,64].…”
Section: Dielectric Dispersion and Relaxation Behaviourmentioning
confidence: 85%
“…Various strategies, such as multilayer structure, electrospinning, heat treatment, etc. were used to improve the performance of the composite films. On the other hand, nanoparticles such as BaTiO 3 and Ba 0.5 Sr 0.5 TiO 3 were utilized to enhance the dielectric and energy storage of PMMA. , The difficulty that needs to be solved for the nanocomposite dielectric films is how to achieve uniform dispersion of nanoparticles in the matrix. In addition to the above methods, copolymerization technology provides another feasible strategy for improving the performance of PMMA.…”
Section: Introductionmentioning
confidence: 99%